PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS IV SD (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low understanding of mathematical concepts of fourth grade elementary school students. This study aims to determine the effect of problem-based learning models assisted by animated video media on the understanding of mathematical concepts of fourth grade elementary school students. This study uses the Quasi Experiment Group Design method with the Nonequivalent Control Group Design type. The study population was 42 students, as well as a sample consisting of students in grades IVA and IVB through saturated sampling techniques. Data collection was carried out through tests, observations, and documentation. Data were analyzed using Independent Samples T-Test. The results showed that there was a significant difference between the understanding of mathematical concepts of students in the experimental and control classes. This is evidenced by the significance value of the Independent Samples T-Test of 0.009 <0.05. Therefore, the Problem-Based Learning model with animated video media affects the mathematical concept understanding of fourth-grade elementary school students.